Drag me to Hell [videorecording (DVD)] - Raimi, Sam; Lohman, Alison, 1979-; Long, Justin, 1978-; Raver, Lorna; Rao, Dileep; Paymer, David (Universal Studios Home Entertainment, 2009)
Christine Brown is an ambitious L.A. loan officer. She is on a desperate quest to break an evil curse. Professor Clay Dalton is her charming boyfriend. Life is good until the mysterious Mrs. Ganush arrives at the bank to beg for an extension on her home loan. Christine denies the extension to impress her boss and get a leg-up on a promotion, shaming Mrs. Ganush and dispossessing her of her home. She finds herself the recipient of a supernatural curse, which turns her life into a living hell.